ANTIPYRETIC ACTIVITY AND ACUTE TOXICITY OF PHOSPHOROUS CONTAINING SALICYLATES - Brel, A. K.; Lisina, S. V. (Malaysian Journal of Science, 2014)
New phosphorous-containing salicylates and two allyl salicylates with pharmacological potential, derived from salicylic acid, have been synthesized. Their chemical structure has been established by spectral analyses (mass spectra and 1H-NMR). The salicylates presented low toxicity, also showing a remarkable antipyretic activity, greater than that of acetylsalicylic acid (aspirin). Partition coefficient (log P), and dissociation constant (pKa) were calculated by the use of ACDLabs system software. The obtained values were correlated with experimental data of activity. Keywords: salicylates, antipyretic activity, acute toxicity.